2020
DOI: 10.3390/publications8010007
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing Research Trends—A Scientometric Approach Using Gunshot Residue (GSR) Literature as an Example

Abstract: The ability to manage, distil and disseminate the significant amount of information that is available from published literature is fast becoming a core and critical skill across all research domains, including that of forensic science. In this study, a simplified scientometric approach has been applied to available literature on gunshot residue (GSR) as a test evidence type aiming to evaluate publication trends and explore the interconnectivity between authors. A total of 731 publications were retrieved using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…The Index keywords provided by Scopus are specific to the database and they will differ from lists available in other databases. Sobreira et al combined both the Authors and the Index keywords to populate the keywords figure while acknowledging the bias such an approach creates (Sobreira et al, 2020). However, since six reference lists (i.e., explosives analysis and scene, fingermarks composition and detection, and toxicology challenges‐advances and surveillance) were created from the references given for three evidence types (explosives, fingermarks, and toxicology), it is reasonable to assume multiple keywords will be shared between the related reference list pairs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Index keywords provided by Scopus are specific to the database and they will differ from lists available in other databases. Sobreira et al combined both the Authors and the Index keywords to populate the keywords figure while acknowledging the bias such an approach creates (Sobreira et al, 2020). However, since six reference lists (i.e., explosives analysis and scene, fingermarks composition and detection, and toxicology challenges‐advances and surveillance) were created from the references given for three evidence types (explosives, fingermarks, and toxicology), it is reasonable to assume multiple keywords will be shared between the related reference list pairs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Raghunath investigated five topics in forensic science and identified associations between forensic anthropology, genetics, medicine, and toxicology (Raghunath, 2018). An analysis of the literature on gunshot residue was reported by Sobreira et al which focused on keywords and cross citation in addition to co-authorship and countries of origin to determine research trends and the evolution of the research base (Sobreira et al, 2020). Finally, with the growing user presence on digital platforms, studies summarizing the current research trends in digital forensics have been reported for digital imaging (Baldwin et al, 2018) and cloud forensics (Gokhale et al, 2020).…”
mentioning
confidence: 99%
“…This method is helpful for researchers who are interested in but unfamiliar with a specific field to understand the status of this field quickly. Various bibliometric studies have explored different topics related to climate change ( Demiroglu and Hall, 2020 ), global warming ( Marx et al., 2017 ), climate change's impact on human health, agriculture, and water resource management ( Wang et al., 2014 ; Janssen et al., 2006 ; Li et al., 2011 ; Wei et al., 2015 ), and various scientific ( Oliveira et al., 2020 ) and technological ( Sobreira et al., 2020 ) questions. Studies that merge traditional bibliometrics with scientific topics also term these types of studies scientometrics ( Janmaijaya et al., 2018 ; Sobreira et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various bibliometric studies have explored different topics related to climate change ( Demiroglu and Hall, 2020 ), global warming ( Marx et al., 2017 ), climate change's impact on human health, agriculture, and water resource management ( Wang et al., 2014 ; Janssen et al., 2006 ; Li et al., 2011 ; Wei et al., 2015 ), and various scientific ( Oliveira et al., 2020 ) and technological ( Sobreira et al., 2020 ) questions. Studies that merge traditional bibliometrics with scientific topics also term these types of studies scientometrics ( Janmaijaya et al., 2018 ; Sobreira et al., 2020 ). Such studies often rely on the most comprehensive literature databases available, including Web of Science and Scopus ( Sobreira et al., 2020 ; Salmerón-Manzano and Manzano-Agugliaro, 2017 ; Macchi Silva et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation